A wave parameters and directional spectrum analysis for extreme winds (2013)
In this research a comparison between two of the most popular ocean wave models, WAVEWATCH III™ and SWAN, was performed using data from hurricane Katrina in the Gulf of Mexico. The numerical simulation of sea surface directional wave spectrum and other wave parameters for several parameter- izations and its relation with the drag coefﬁcient was carried out. The simulated data were compared with in-situ NOAA buoy data. For most of the buoys, WAVEWATCH III™ presented the best statistical comparisons for the main wave parameters, such as signiﬁcant wave height and peak period. The SWAN model tends to overestimate the maximum values for signiﬁcant wave height for some buoys and the peak period for almost all the buoys. Both models tend to overestimate the value of peak direction, presenting an area of greater energy to the south. The WAVEWATCH III™ model performs best for buoys located in right forward quadrant, which generally has higher winds and waves. This indicates a better spatial representation of wave parameters in the higher energy areas for the WAVEWATCH III™ model. Results based on the quadrant location for most of the analyzed cases, are in agreement with the results from other sources such as the Scanning Radar Altimeter (SRA).